Sustainability of Coastal Community-Based Ecotourism in Trang Province - Rojchanaprasart, Natthita; Tinnungwattana, Wipawan; Tongnunui, Prasert (Kasetsart Journal of Social Sciences, 2015)
The objective of this research was to study the sustainability of ecotourism in coastal communities in Trang province, Thailand. The target groups were community tourism leaders, stakeholders (such as the Subdistrict Administration Organization, staff of the Office of Tourism and Sports, staff of Non-Government Organizations), and tourists staying in four homestays. The homestays were Yong Star homestay, Bho Hin farmstay, Kho Libong homestay, and Kho Muk homestay. The data were collected using in-depth interviews, a sharing forum, and a questionnaire. From the results, the sustainability of coastal community-based ecotourism could be considered from an output/outcome dimension. There were agreements between the evaluation results for both communities and tourists. From the total score of 5.00, ranking of the overall sustainability was at the high level (X̅ = 4.04 and 3.82, respectively) along with the effectiveness of tourism management in the community (X̅ = 4.01 and 3.78, respectively), and the impact of tourism management on the community (X̅ = 4.06 and 3.85, respectively). However, these sustainability levels were affected by three dimensions: context, communities’ social capital and process dimensions.